2017
DOI: 10.1093/molbev/msx156
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation Profiling Reveals Epigenetic Adaptation of Stickleback to Marine and Freshwater Conditions

Abstract: The three-spined stickleback (Gasterosteus aculeatus) represents a convenient model to study microevolution-adaptation to a freshwater environment. Although genetic adaptations to freshwater environments are well-studied, epigenetic adaptations have attracted little attention. In this work, we investigated the role of DNA methylation in the adaptation of the marine stickleback population to freshwater conditions. DNA methylation profiling was performed in marine and freshwater populations of sticklebacks, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
124
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(134 citation statements)
references
References 27 publications
10
124
0
Order By: Relevance
“…Furthermore, it has been shown that salt-induced alterations in DNA methylation patterns play a role in sea water adaptation in fishes (Artemov et al, 2017;Moran, Marco-Rius, Megías, Covelo-Soto, & Pérez-Figueroa, 2013). One may hypothesize that early environmental factors may also influence life-history decisions and phenotypic plasticity in brown trout, although this has not yet been investigated.…”
Section: Epigeneticsmentioning
confidence: 99%
“…Furthermore, it has been shown that salt-induced alterations in DNA methylation patterns play a role in sea water adaptation in fishes (Artemov et al, 2017;Moran, Marco-Rius, Megías, Covelo-Soto, & Pérez-Figueroa, 2013). One may hypothesize that early environmental factors may also influence life-history decisions and phenotypic plasticity in brown trout, although this has not yet been investigated.…”
Section: Epigeneticsmentioning
confidence: 99%
“…An exception is the study of Artemov et al. (), who investigated the role of DNA methylation in the adaptation of populations of the marine stickleback ( Gasterosteus aculeatus ) to freshwater conditions. Notably, the DNA methylation profile of marine sticklebacks transferred into freshwater partially converged to that of a freshwater stickleback, with the genes encoding ion channels (KCND3, CACNA1FB and ATP4A) being differentially methylated between the marine and the freshwater populations.…”
Section: Epigenetic Contribution For the Adaptation To Climate Changementioning
confidence: 99%
“…For example, Kumar and Wigge (2010) showed that the short- Varriale (2014) The levels of methylation of warm-blooded species were consistently lower than those of the cold-blooded vertebrates Garg, Chevala, Shankar, and Jain (2015) Reported that the role of DNA methylation patterns are typically associated with genes important for abiotic stress responses in three rice (Oryza sativa) cultivars (IR64, stresssensitive; Nagina 22, drought-tolerant; Pokkali, salinity-tolerant) Artemov et al (2017) Genes encoding ion channels (KCND3, CACNA1FB and ATP4A) were differentially methylated between a marine and the freshwater populations of the winter skate (Leucoraja ocellata) Sun et al (2016) Both females and males from the Nile tilapia (Oreochromis niloticus) showed an increase in methylation levels on various chromosomes after high-temperature exposure Lighten et al (2016) Epigenetic mechanisms determined the different profiles of gene expression and life-history traits of two recently diverged populations of the winter skate (Leucoraja ocellata)…”
Section: Adaptation To Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation has been implicated in mediating ecologically relevant traits in response to varied environmental conditions (Artemov et al, ; Baerwald et al, ; Lea, Altmann, Alberts, & Tung, ), primarily due to its regulatory relationship with gene expression, particularly around CpG islands that are dense clusters of cytosine‐guanine dinucleotides (Fujita et al, ; Lorincz, Dickerson, Schmitt, & Groudine, ; Maunakea et al, ). If heritable epigenetic modifications are imparted by specific environments, and these modifications increase fitness regardless of underlying genetic sequence (Herman & Sultan, ), then these epigenetic loci have important long‐term evolutionary consequences (Hu & Barrett, ).…”
Section: Introductionmentioning
confidence: 99%